Panthera tigris amoyensis Genomic DNA Extraction with simplified method - Jinghua Ma; Yukun Jia; Ying Lin; Xianfu Zhang; Xianyu Yang (IJRDO-Journal of Applied Science, 2019)
Nowadays, eukaryotic genomic DNA is mainly extracted by its corresponding kits purchased from many companies. In this paper, a method for isolation of Panthera tigris amoyensis genomic DNA has been tried, which is really simple and quick.